5g+4(-8+5g)=1-g

Simple and best practice solution for 5g+4(-8+5g)=1-g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5g+4(-8+5g)=1-g equation:


Simplifying
5g + 4(-8 + 5g) = 1 + -1g
5g + (-8 * 4 + 5g * 4) = 1 + -1g
5g + (-32 + 20g) = 1 + -1g

Reorder the terms:
-32 + 5g + 20g = 1 + -1g

Combine like terms: 5g + 20g = 25g
-32 + 25g = 1 + -1g

Solving
-32 + 25g = 1 + -1g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add 'g' to each side of the equation.
-32 + 25g + g = 1 + -1g + g

Combine like terms: 25g + g = 26g
-32 + 26g = 1 + -1g + g

Combine like terms: -1g + g = 0
-32 + 26g = 1 + 0
-32 + 26g = 1

Add '32' to each side of the equation.
-32 + 32 + 26g = 1 + 32

Combine like terms: -32 + 32 = 0
0 + 26g = 1 + 32
26g = 1 + 32

Combine like terms: 1 + 32 = 33
26g = 33

Divide each side by '26'.
g = 1.269230769

Simplifying
g = 1.269230769

See similar equations:

| 74y-4884=y+(-72) | | 74y-4884=y+(-74) | | A-10=34 | | 16x-1.86x^2=0 | | (3x^2-5x)-(x^2+4x+3)= | | y=20+5x | | A=2400+144t | | 2(6z+1)-6=92 | | 7/8=y/56 | | 1.5y=1.25 | | 2h+7=2(h+2)+3 | | x-x/5=44 | | k/4=0.3 | | 4x+11=7x-5 | | 72x-17=72/x | | 3(4+3x)=66 | | 4-0.3q=-0.3+4 | | S=v+ay | | 5x+7y=295 | | y=30(x-4)+1 | | -.13z-.38=.5z-3 | | X-3/8=9/4 | | 4-0.4q=-0.4+4 | | 4/x-7=-5 | | .01x=17 | | 1.1y+2.2= | | -4p+9+5p=15 | | 1x+16x-76=24 | | 3x=4x+15 | | 15-24u=u+15 | | 0=-16t^2+160t+8 | | y+6x=9 |

Equations solver categories